2012
DOI: 10.1002/cmr.a.21249
|View full text |Cite
|
Sign up to set email alerts
|

Super‐resolution in magnetic resonance imaging: A review

Abstract: For the last 15 years, super‐resolution (SR) algorithms have successfully been applied to magnetic resonance imaging (MRI) data to increase the spatial resolution of scans after acquisition has been performed, thus facilitating the doctors' diagnosis. The variety of application and techniques has grown ever since, especially in the MRI modality, showing the interest of the community to such postacquisition processing. This article presents a review of the general principle of SR as well as how this principle h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
175
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(176 citation statements)
references
References 115 publications
1
175
0
Order By: Relevance
“…7 x 0 .7mm3 using zero-padding. However zero-padding is similar to performing interpolation in image space and is known to introduce blur and diminish contrast (Van Reeth et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 x 0 .7mm3 using zero-padding. However zero-padding is similar to performing interpolation in image space and is known to introduce blur and diminish contrast (Van Reeth et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This strategy was then extended to arbitrary orientations (Poot et al, 2010) and applied to DW images . Reviews and comparisons of some of these methods can be found in (Plenge et al, 2012;Van Reeth et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Improving the system machinery by, for example, increasing the number of coil receiver channels or the magnetic field strength can increase signal strength. 60 Longer acquisition times also increase resolution, although this may be hampered by the susceptibility of patients to claustrophobia, or the length of time tolerated by an animal in the machine. 61 Should cost, time available for image acquisition, or movement of a subject be prohibitive, imageprocessing techniques can be applied postscanning.…”
Section: Magnetic Resonance Imaging: Imaging With Magnetismmentioning
confidence: 99%
“…While superresolution algorithms have been applied in uni-modal settings [22], they have not been widely explored for multimodal neuroimaging. We fill this gap by introducing BRAINZOOM, a novel method for super-resolution reconstruction of brain activity by combining different modalities of brain imaging.…”
Section: Introductionmentioning
confidence: 99%